Application of nitrate to enhance biodegradation of gasoline components in soil by indigenous microorganisms under anoxic condition. Issue 9 (2nd May 2016) - Yang, Su-Cai; Song, Yun; Wang, Dong; Wei, Wen-Xia; Yang, Yan; Men, Bin; Li, Jia-Bin
ABSTRACT: Anaerobic/anoxic biodegradation of hydrocarbons offers an attractive approach to the removal of these compounds from polluted environments such as aquifers, aquatic sediments, submerged soils and subsurface soils. The application of nitrate was investigated to accelerate the degradation of gasoline components such as mono-aromatic hydrocarbons and total petroleum hydrocarbons (TPH) in soil by indigenous microorganisms under anoxic condition. The addition of nitrate had little effect on the degradation of mono-aromatic hydrocarbons m- & p -xylene, o -xylene, sec -butylbenzene and 1, 2, 4-trimethylbenzene, but facilitated the degradation of TPH (C6 –C12 ) and mono-aromatic hydrocarbons toluene and ethylbenzene markedly. Furthermore, the more nitrate added, the higher the percentage of toluene, ethylbenzene and TPH (C6 –C12 ) degraded after 180 days of anoxic incubation. Microorganisms capable of degrading toluene, ethylbenzene and TPH (C6 –C12 ) with nitrate as the electron acceptor under anaerobic/anoxic condition are composed predominantly of Alpha-, Beta-, Gamma- or Delta-proteobacteria . Beta- and Gamma-proteobacteria were the main components of indigenous microorganisms, and accounted for 83–100% of the total amount of indigenous microorganisms in soil used in this study. Furthermore, the total amount of indigenous microorganisms increased with nitrate added. The addition of nitrate stimulated the growth of indigenous microorganisms, and therefore facilitated the degradation of toluene, ethylbenzene and TPH (C6 –C12 ).